(3GdOQQ GdaQGFO ef ZQQ GdbdGFOs - (3CHhGdYHGS CMeO Hf jMji Hf aVd Gddg GdYeQj TgGH GdOjfs; (3GHf NGbGf , CHh fUQ,J (B528 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi QGV dfG GdHjGf MJi EfbGO ai CZfJfG s
(3BNQgG (B:s
(3hjegd GdcGaQ Mceg ef Gddg hYdekG, hEfeG fedj dge djROGOh EKeG ced ENJjGQ cJGH bdGFO GdYbjGf, Ydi jO cGJHg CMeO Hf jMji Hf aVd Gddg GdYeQj YaGGddg Yfg aj Pj GdMLI SfI YTQjf hSHYeGFI s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B134 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B49s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B176 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B170 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs